2018
DOI: 10.1136/bmjopen-2018-022970
|View full text |Cite
|
Sign up to set email alerts
|

Patient trajectories and their impact on mobility, social participation and quality of life in patients with vertigo/dizziness/balance disorders and osteoarthritis (MobilE-TRA): study protocol of an observational, practice-based cohort study

Abstract: IntroductionMobility limitations have a multitude of different negative consequences on elderly patients including decreasing opportunities for social participation, increasing the risk for morbidity and mortality. However, current healthcare has several shortcomings regarding mobility sustainment of older adults, namely a narrow focus on the underlying pathology, fragmentation of care across services and health professions and deficiencies in personalising care based on patients’ needs and experiences. A tail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…Sample size calculation was informed by data of a cohort study with the same population [ 32 ]. Data gave evidence of an ICC = 0.04 and an expected standard deviation of 25.…”
Section: Methodsmentioning
confidence: 99%
“…Sample size calculation was informed by data of a cohort study with the same population [ 32 ]. Data gave evidence of an ICC = 0.04 and an expected standard deviation of 25.…”
Section: Methodsmentioning
confidence: 99%
“…Data for this research project emanated from the longitudinal multicenter study MobilE-TRA conducted in two German federal states (Bavaria and Saxony) from September 2017 until October 2019. A more detailed description of the study can be found elsewhere [ 18 ]. In brief, patients aged 65 years and older were included if they had consulted their PCP for an acute episode of VDB in the last quarter.…”
Section: Methodsmentioning
confidence: 99%
“…5 In the 5th decade following the 7th and 4th decades, incidence of vertigo found was more common in patient. Women (57.7%) were found to be more frequently affected than men (42.30%) in the 4:3 ratio 6 .…”
Section: Introductionmentioning
confidence: 93%
“…When testing horizontal semi-circular canals, the head is flexed 30 degree. In the case of a low amplitude (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) of either a moderate amplitude (approximately 200/sec) and high amplitude with an angular momentum (3000-4000/ sec), the eyes turn in a direction opposite to the head movement and the focus stays in a manual direction, while the Vestibular Reflex is working in a normal way. In a patient with a loss of vestibular function, the person will not move the eyes rapidly from the target as the head and eyes move away from target.…”
Section: Head Impulse Testmentioning
confidence: 99%